Comparison of the common carotid arteries of horses and mules by B-mode and Doppler spectral ultrasonography and the relation with body mass - Fogaca, J. L. [UNESP]; Castiglioni, M. C. R. [UNESP]; Vettorato, M. C. [UNESP]; Silva, J. P. [UNESP]; Mazzante, N. M. G. [UNESP]; Filadelpho, A. L. [UNESP]; Puoli Filho, J. N. P. [UNESP]; Machado, V. M. V. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
Conventional ultrasound and spectral Doppler in the common carotid arteries in horses and mules are considered scarce, different from human medicine. The aim of this study was to compare the common carotid arteries of horses and mules by B-mode ultrasonography and spectral Doppler ultrasonography, as well as to verify the differences of these variables between their genders and the relation with body mass. The following parameters were evaluated: body mass, artery diameter, intima-media thickness (EIM), resistivity index (IR), pulsatility index (IP), systolic velocity (VS), diastolic velocity (VD) and average velocity (VM). Besides the body mass, the other variables were obtained from three regions (cranial, medium and caudal) and analyzed together. The diameters of the common carotid arteries are different between horses and mules, being smaller in horses. The IR, IP, VS and T7/14 differed between horses and mules, being higher in the horses, but the VD was higher in mules. No difference in the variables in B-mode and Doppler between gender were observed in horses, different from mules, in which the diameters, IR and IP values were higher in males and the VS and T7/14 was higher in females. Body mass did not influence B-Mode, both for horses and mules. A significant correlation was observed for Doppler. The common carotid arteries of horses and mules are different by ultrasound scans B-mode and spectral Doppler. Gender does not influence the B-Mode and Doppler variables in horses, but can in mules. The body mass of horses and mules, regardless of gender, is not associated with B-mode variables, but with Doppler variables.
Keywords: ulfrasound; carotid arterial flow; equines; gender